2018
DOI: 10.1007/s00213-018-4976-7
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-induced conditioned place preference negatively correlates with anxiety-like behavior in adolescent mice: inhibition by a neurokinin-1 receptor antagonist

Abstract: The present results highlight the negative correlation between anxiety-like behavior and the propensity for alcohol and the critical role for NK1R in alcohol reward in adolescent mice. Importantly, the NK1R antagonist L-703,606 might be a promising therapeutic target for alcohol use disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…In fact, and after a period of conditioning, the mice spent significantly more time in the chamber paired with EtOH. These results are consistent with earlier studies, from our laboratory (Al Bahi and Dreyer 2014;Bahi et al 2014b) and from others, in which 2 g kg −1 EtOH elicited a robust CPP in both mice (Huang et al 2018;Marcus et al 2017;Xie et al 2019), and rats (Fu et al 2016;Okhuarobo et al 2018;Zuo et al 2017). Next, we found, in the 1st experiment, that repeated daily exposure to both conditioning chambers successfully extinguished this CPP.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, and after a period of conditioning, the mice spent significantly more time in the chamber paired with EtOH. These results are consistent with earlier studies, from our laboratory (Al Bahi and Dreyer 2014;Bahi et al 2014b) and from others, in which 2 g kg −1 EtOH elicited a robust CPP in both mice (Huang et al 2018;Marcus et al 2017;Xie et al 2019), and rats (Fu et al 2016;Okhuarobo et al 2018;Zuo et al 2017). Next, we found, in the 1st experiment, that repeated daily exposure to both conditioning chambers successfully extinguished this CPP.…”
Section: Discussionsupporting
confidence: 93%
“…Over 35 generations later, bHR and bLR rats exhibited all of the key features of the outbred HR/LR rats while also exhibiting correlated differences in low anxiety‐like, or risk‐taking behaviors during EPM, LDB, and OFA paradigms 17 . Analogous to the HR/LR rat lines, Huang et al 19 used the EPM to assess the anxiety‐like behavior of C57BL/6J mice and afterwards separated the mice into HAM and LAM groups. Finally, similar to the bHR/bLR rat lines, Krömer et al 18 created a high (HAB), normal (NAB), and low (LAB) anxiety‐related behavior mouse model by selectively inbreeding outbred CD‐1 mice based on their behavior in the EPM for over 15 generations.…”
Section: Discussionmentioning
confidence: 99%
“…17 Additionally, Krömer et al 18 utilized the EPM to create CD-1 mouse models of high (HAB), normal (NAB), and low (LAB) anxiety behaviors. Finally, Huang et al 19 performed a similar paradigm to create C57BL/6J high (HAM) and low (LAM) anxiety mouse models.…”
mentioning
confidence: 99%
“…In addition, Ribeiro and De Lima (2002) demonstrated that NKR2 antagonists can block the anxiogenic effects of pentylenetetrazol. Combined, these data may suggest a role for NKRs in anxiety and alcohol reward in adolescent mice (Huang et al, 2018) that may also be important in this rat model of adolescent binge drinking.…”
Section: Discussionmentioning
confidence: 88%
“…Tachykinin receptors (TACR2, TACR3) encode for tachykinin neuropeptide substance K (NK2 and NK3). Huang et al (2018) showed that low-anxiety mice have a greater preference for ethanol when compared to the high-anxiety mouse group. Low-anxiety mice also had higher levels of NK1 receptor (NKR1) in the hippocampus when compared to the high-anxiety group.…”
Section: Addictionmentioning
confidence: 99%